The targeting of β‐cells by T lymphocytes in human type 1 diabetes: clinical perspectives. (4th September 2013) - Luce, S.; Briet, C.; Bécourt, C.; Lemonnier, F.; Boitard, C.
Abstract : This review focuses on genes that control β‐cell targeting in autoimmune, type 1‐dependent, diabetes (T1D) and on insulin as the major autoantigen recognized by T lymphocytes throughout the disease process. T1D associates with multiple gene variants. Beyond genes that predispose to general failure of immune tolerance to self, loci identified by the analysis of crosses between non‐obese diabetic (NOD) and conventional mouse strains harbour genes that control β‐cell targeting or the deviation of autoimmunity towards other tissues. We report here the role of genes encoding co‐activation molecules involved in the activation of T lymphocytes, ICOS and ICOS ligand (B7RP1). NOD mice which are deficient in either of these two molecules are protected from diabetes, but instead develop a neuromuscular autoimmune disease. We also report the characterization in humans of T lymphocytes that are specific for major β‐cell autoantigens, especially insulin. This opens the way towards new bioassays in the diagnosis of autoimmunity and towards autoantigen‐specific immunotherapy in T1D. In order to develop a new preclinical model of T1D that would allow testing insulin epitopes to induce immune tolerance in vivo, we developed a mouse that is deficient in endogenous major histocompatibility complex class I and class II genes and deficient for the two murine insulin genes and that express human class I, class II and insulin genes.